2002
DOI: 10.1038/sj.jea.7500212
|View full text |Cite
|
Sign up to set email alerts
|

Estimating particle exposure in the Mexico City metropolitan area

Abstract: Study question: We examined whether methods for measuring exposure to airborne particles less than 10 m in aerodynamic diameter ( PM 10 ) in the Mexico City metropolitan area give different estimates of PM 10 levels, and the nature of these differences, and developed a model for estimating missing PM 10 data for one measurement method. Methods: Government PM 10 measurements using two different technologies at five sites ( the Sierra -Anderson PM 10 HighVolume Air Sampler System, Hi -Vol ) ( every sixth day ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…PNC data were not directly available for the study period, but were retrospectively estimated from one monitoring station from 2001-2002. The statistical model predicts PNC well, and our estimation procedure was certainly superior (in terms of R 2 ) to what has been done to estimate PM 10 or PM 2.5 in previous studies (49)(50)(51)(52)(53)(54)(55). However, PNC is derived from existing air pollutants, and it is highly correlated to some of them ( Table 2).…”
Section: Discussionmentioning
confidence: 59%
“…PNC data were not directly available for the study period, but were retrospectively estimated from one monitoring station from 2001-2002. The statistical model predicts PNC well, and our estimation procedure was certainly superior (in terms of R 2 ) to what has been done to estimate PM 10 or PM 2.5 in previous studies (49)(50)(51)(52)(53)(54)(55). However, PNC is derived from existing air pollutants, and it is highly correlated to some of them ( Table 2).…”
Section: Discussionmentioning
confidence: 59%
“…We excluded the Xalostoc station in Mexico City. This monitor is near industrial sources (Retama, personal communication, January 2005), as confirmed by systematically high concentration readings and relatively lower correlations with other monitor sites, 28 and is thus not likely to be representative of wider population exposure. Pearson correlations among the selected monitors within each city were all at least 0.50.…”
Section: Environmental Datamentioning
confidence: 90%
“…Data from three different PM 10 metrics were available for comparisons: two from the government of Mexico City (one with daily concentrations, one with every sixth day measures, from 1994 to 1998), and one PM 10 metric from an academic research effort (daily concentrations in 1994 and 1995). In a previous analysis (O'Neill et al, 2002), we found low correlations between the two methods used by the Mexico City government to measure and regulate PM 10 , as well as between one of the government methods and the research group's data. We also found large variation in the mean levels measured by the two government methods, depending on the monitoring site (O'Neill et al, 2002).…”
Section: Air Pollution Datamentioning
confidence: 72%
“…In a previous analysis (O'Neill et al, 2002), we found low correlations between the two methods used by the Mexico City government to measure and regulate PM 10 , as well as between one of the government methods and the research group's data. We also found large variation in the mean levels measured by the two government methods, depending on the monitoring site (O'Neill et al, 2002). We speculated that the observed differences could be important for epidemiology studies of the health impacts of particulate air pollution.…”
Section: Air Pollution Datamentioning
confidence: 72%
See 1 more Smart Citation